2020
DOI: 10.1016/j.biochi.2020.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interactions involving enzymes of the mammalian methionine and homocysteine metabolism

Abstract: Enzymes of the methionine and homocysteine metabolism catalyze reactions belonging to the methionine and folate cycles and the transsulfuration pathway. The importance of the metabolites produced through these routes (e.g. S-adenosylmethionine, homocysteine) and their role in e.g. epigenetics or redox mechanisms makes their tight regulation essential for a correct cellular function. Pharmacological or pathophysiological insults induce, among others, changes in activity, oligomerization, protein levels, subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 130 publications
(290 reference statements)
0
20
0
Order By: Relevance
“…As a precursor of S ‐adenosylmethionine (SAM), a universal methyl donor, a high level of Hcy can lead to the increase in SAM level, which accordingly upregulates the activity of DNMTs using the substrate of DNMT [ 24 , 25 ]. Our previous study showed that DNA methylation can contribute to the development of diseases such as cardiovascular and liver diseases caused by Hcy [ 15 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a precursor of S ‐adenosylmethionine (SAM), a universal methyl donor, a high level of Hcy can lead to the increase in SAM level, which accordingly upregulates the activity of DNMTs using the substrate of DNMT [ 24 , 25 ]. Our previous study showed that DNA methylation can contribute to the development of diseases such as cardiovascular and liver diseases caused by Hcy [ 15 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weak transient interactions associate and dissociate continuously (e.g., high dissociation rate), like most receptor–receptor interactions ( Perkins et al, 2010 ; Acuner Ozbabacan et al, 2011 ). The characterization of these interactions in their native environment has been challenging compared with strong and high-affinity interactions that can be captured by most available biochemical approaches ( Xing et al, 2016 ; Titeca et al, 2019 ; Portillo et al, 2020 ). Different methods are available to investigate the interaction of hydrophobic proteins, such as membrane proteins ( Snider et al, 2015 ).…”
Section: Protein–protein Interactions At the Plasma Membrane: Detection Methodsmentioning
confidence: 99%
“…Homocysteine (Hcy), a sulfur amino acid, is generated during the metabolism of methionine 93 . Hyperhomocysteinemia (HHcy) is an independent risk factor associated with cardiovascular complications such as MI 94 .…”
Section: Targeting Er Stress By H2s In Different Cardiac Disordersmentioning
confidence: 99%
“…Homocysteine (Hcy), a sulfur amino acid, is generated during the metabolism of methionine. 93 Hyperhomocysteinemia (HHcy) is an independent risk factor associated with cardiovascular complications such as MI. 94 HHcy can induce myocardial oxidative stress, 95 hypomethylation, 96 and ER stress-mediated apoptosis.…”
Section: Targeting Er Stress By H 2 S In Hyperhomocysteinemia-induced...mentioning
confidence: 99%